Pembuatan Ekoenzim Berbasis Limbah Kulit Pisang (Musa Paradisiaca) secara Anaerob dan Aplikasinya pada Crude Palm Oil (CPO) - Yudi Romaito Rambe; Zakwan Zakwan (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
High levels of free fatty acids (FFA) in crude palm oil (CPO) are one of the main problems in the palm oil industry because they can reduce product quality and export competitiveness. On the other hand, abundant banana peel waste has not been optimally utilized, even though it contains various bioactive compounds that have the potential to be used as raw materials for eco-enzymes. This study aims to produce ecoenzymes based on banana peel waste (Musa paradisiaca) through anaerobic fermentation and to evaluate their effect on reducing FFA and moisture content in CPO. The study employed an experimental design using a non-factorial Complete Randomized Design (CRD). The ecoenzyme was prepared using a banana peel:molasses:water ratio of 3:1:10 and fermented for 90 days. The ecoenzyme was applied to CPO in three treatments—5 mL, 10 mL, and 15 mL—each with three replicates. The results showed that the resulting ecoenzyme had a pH of 3.40, a TDS of 3,922 ppm, and a temperature of 31°C. The initial ALB content of CPO, which was 26.47%, was successfully reduced to 14.83%, 12.75%, and 10.69% in the 5 mL, 10 mL, and 15 mL treatments, respectively. Statistical analysis showed that all treatments had a significant effect on reducing ALB (p<0.05). Thus, banana peel waste-based ecoenzymes have the potential to serve as an environmentally friendly alternative for reducing ALB levels in CPO while supporting the sustainable utilization of organic waste.